2019
DOI: 10.1021/acs.inorgchem.9b02176
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Adsorption in a Redox-Active Metal–Organic Framework: Electrical Conductivity Induced by Host−Guest Charge-Transfer

Abstract: We report a comparative study of the binding of I2 (iodine) in a pair of redox-active metal–organic framework (MOF) materials, MFM-300(VIII) and its oxidized, deprotonated analogue, MFM-300(VIV). Adsorption of I2 in MFM-300(VIII) triggers a host-to-guest charge-transfer, accompanied by a partial (∼30%) oxidation of the VIII centers in the host framework and formation of I3– species residing in the MOF channels. Importantly, this charge-transfer induces a significant enhancement in the electrical conductivity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 35 publications
3
61
0
Order By: Relevance
“…The 1 H NMR spectrum showed three signals at 8.74 ppm, 8.46 ppm, and 8.06 ppm, which can be assigned to the benzene ring with m-substituted groups. To provide additional proof, 13 C CP-MAS NMR analysis of macrocyclic organic compounds was employed. As shown in the Figures S5-S6, broad peaks between 129 ppm and 146 ppm were assigned to the aromatic carbon atoms of the structures.…”
Section: Materials Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H NMR spectrum showed three signals at 8.74 ppm, 8.46 ppm, and 8.06 ppm, which can be assigned to the benzene ring with m-substituted groups. To provide additional proof, 13 C CP-MAS NMR analysis of macrocyclic organic compounds was employed. As shown in the Figures S5-S6, broad peaks between 129 ppm and 146 ppm were assigned to the aromatic carbon atoms of the structures.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…[9][10][11] Iodine capture materials not only should have good chemical and thermal stability, [12] but also have selectivity and durability for radioactive iodine. [13] Up to now, different kinds of porous materials have been used for gas absorption, guest molecules and I 2 capture, such as metal-organic frameworks (MOFs), [14][15][16][17][18] covalent organic frameworks (COFs), [19,20] supramolecular organic frameworks (SOFs), [21][22][23] porous organic cages, [24] and porous organic polymers. [2,25,26] Most of the porous iodine adsorption materials have the advantage of high adsorption capacity.…”
mentioning
confidence: 99%
“…Iodine doping in porous materials typically exploits a charge transfer (CT) mechanism that introduces a labile charge transport material that is affected by the microenvironment and redox activity (I 2 and TCNQ) [55–60] . For instance, it has been reported that iodine doping in porous materials resulted in enhanced conductivity due to I 2 ‐ligand interactions (e.g., CT complex formation), [61, 62] a Grotthuss‐like charge transport mechanism, [63–65] or through metal oxidation in framework nodes [55, 66] . In the presented studies, Th 4+ and Zr 4+ in metal nodes cannot be further oxidized, and therefore, conductivity enhancement likely originates from I 2 ‐ligand interactions [61, 62] .…”
Section: Resultsmentioning
confidence: 90%
“…[32,33] Iodine doping in porous materials typically exploits acharge transfer (CT) mechanism that introduces al abile charge transport material that is affected by the microenvironment and redox activity (I 2 and TCNQ). [55][56][57][58][59][60] Forinstance,ithas been reported that iodine doping in porous materials resulted in enhanced conductivity due to I 2 -ligand interactions (e.g., CT complex formation), [61,62] aG rotthuss-like charge transport mechanism, [63][64][65] or through metal oxidation in framework nodes. [55,66] In the presented studies,T h 4+ and Zr 4+ in metal nodes cannot be further oxidized, and therefore,conductivity enhancement likely originates from I 2 -ligand interactions.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…[55][56][57][58][59][60] Forinstance,ithas been reported that iodine doping in porous materials resulted in enhanced conductivity due to I 2 -ligand interactions (e.g., CT complex formation), [61,62] aG rotthuss-like charge transport mechanism, [63][64][65] or through metal oxidation in framework nodes. [55,66] In the presented studies,T h 4+ and Zr 4+ in metal nodes cannot be further oxidized, and therefore,conductivity enhancement likely originates from I 2 -ligand interactions. [61,62] In as imilar vein, TCNQ is aw ell-studied electron acceptor and introduction of which commonly results in the formation of CT complexes.…”
Section: Forschungsartikelmentioning
confidence: 99%